2019
DOI: 10.1038/s41419-019-2181-1
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel induces lymphatic endothelial cells autophagy to promote metastasis

Abstract: Cytotoxic therapy for breast cancer inhibits the growth of primary tumors, but promotes metastasis to the sentinel lymph nodes through the lymphatic system. However, the effect of first-line chemotherapy on the lymphatic endothelium has been poorly investigated. In this study, we determined that paclitaxel, the anti-cancer drug approved for the treatment of metastatic or locally advanced breast cancer, induces lymphatic endothelial cell (LEC) autophagy to increase metastases. While paclitaxel treatment was lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…It is possible that oxLDL stimulates autophagy in LEC, which leads to decreased AKT expression. In addition, Zamora et al suggested a negative association between lymphangiogenesis and autophagy [ 61 ]. Future studies are required to investigate the effects of oxLDL treatment on autophagy in LEC.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that oxLDL stimulates autophagy in LEC, which leads to decreased AKT expression. In addition, Zamora et al suggested a negative association between lymphangiogenesis and autophagy [ 61 ]. Future studies are required to investigate the effects of oxLDL treatment on autophagy in LEC.…”
Section: Discussionmentioning
confidence: 99%
“…Various modes of action have been proposed to explain the therapeutic and/or adverse effects of CQ and HCQ in COVID-19 patients, although most of the evidence is based on in vitro studies. CQ is a potent inhibitor of autophagy [20][21][22][23] and cell death 24,25 , affecting distinct cell function 26,27 and survival 28,29 , and its derivative HCQ 30 has similar properties inhibiting autophagy. In vitro experiments in tissue culture have shown that CQ and HCQ can increase endosomal pH, prevent virus-cell fusion, and interfere with glycosylation of the ACE2 receptor and thus the binding of the SARS-CoV-2 S protein to ACE2 31 (Fig.…”
Section: Hcq Exerts Strong Immunomodulatory Effectsmentioning
confidence: 99%
“…The matter of CQ, a powerful regulator of endosomal pH in autophagy [10][11][12][13] and cell death 14,15 , affecting distinct cell function 16,17 and survival 18,19 , and of its derivative hydroxychloroquine (HCQ) 20 , has peculiar aspects: they are widely used in patients affected by the COVID-19 disease and reports from hospitals and doctors who treat patients frequently suggest beneficial effects. However, major medical institutions tend to recommend a cautious use, also pointing at dangerous side effects.…”
mentioning
confidence: 99%